2022
DOI: 10.2147/bctt.s363114
|View full text |Cite
|
Sign up to set email alerts
|

Ovo Like Zinc Finger 2 (OVOL2) Suppresses Breast Cancer Stem Cell Traits and Correlates with Immune Cells Infiltration

Abstract: Background Breast cancer stem cells (BCSCs) are associated with tumor initiation, invasion, metastasis and drug resistance. It is known that many proteins and signaling pathways are involved in the regulation of BCSCs, however, much more efforts are needed to understand BCSCs comprehensively. Tumor-infiltrating immune cells are important in cancer treatment efficacy and patient prognosis. We tried to identify potential suppressor of BCSCs and analyze its correlation with various immune cells infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Garcia et al have also shown that Ovol1 and Ovol2 modify the transcriptome of mesenchymal breast cancers cells by downregulation of the mesenchymal markers [72]. Moreover, Wu et al have shown that OVOL2 suppressed stem cells population (CD44+/CD24−) in mesenchymal MDA-MB-231 cells [73]. We have also found a high number of CD44+/CD24− cells in BrC4f CAFs and in cells with transitional phenotypes (Figure S4) that may correlate with their potential to migrate to distant metastatic locuses.…”
Section: Discussionmentioning
confidence: 99%
“…Garcia et al have also shown that Ovol1 and Ovol2 modify the transcriptome of mesenchymal breast cancers cells by downregulation of the mesenchymal markers [72]. Moreover, Wu et al have shown that OVOL2 suppressed stem cells population (CD44+/CD24−) in mesenchymal MDA-MB-231 cells [73]. We have also found a high number of CD44+/CD24− cells in BrC4f CAFs and in cells with transitional phenotypes (Figure S4) that may correlate with their potential to migrate to distant metastatic locuses.…”
Section: Discussionmentioning
confidence: 99%